Barbarism and civilization : a history of Europe in our time - Wasserstein, Bernard (Oxford ; New York : Oxford University Press, 2009)
Historian Bernard Wasserstein offers the first serious, full-length history of a century of convulsive change. It is a history of cruelty and tenderness, of technological achievement and environmental blight, of imperial expansion and withdrawal, of authoritarian repression and of individual rebirth. Wasserstein provides both a narrative of the main contours of the political, diplomatic, and military history and an analysis of the underpinnings of demographic, economic, and social developments. Most notably, the book explores the evolution of values and sensibilities in a period when, for the first time, God disappeared as a living presence in the minds of most Europeans. Wasserstein argues that barbarism and civilization were not polar opposites: rather they marched hand in hand. But he also shows that if Europe witnessed some of the most brutish episodes in the recorded history of our species, it also saw incontestable improvements in living conditions for most inhabitants of the continent.--From publisher description
Europe at 1914 -- Europe at war 1914-1917 -- Revolutionary Europe 1917-1921 -- Recovery of the Bourgeoisie 1921-1929 -- Depression and terror 1929-1936 -- Europe in the 1930s -- Spiral into war 1936-1939 -- Hitler triumphant 1939-1942 -- Life and death in wartime -- End of Hitler's Europe 1942-1945 -- Europe partitioned 1945-1949 -- West European recovery 1949-1958 -- Stalin and his heirs 1949-1964 -- Consensus and dissent in Western Europe 1958-1973 -- Europe in the 1960s -- Strife in Communist Europe 1964-1985 -- Stress in liberal Europe 1973-1989 -- The collapse of Communism in Eastern Europe 1985-1991 -- After the fall 1991-2007 -- Europe in the new millennium.
BIBINDX
Keywords: Europe -- History -- 20th century; Europe -- Civilization -- 20th century